Essential philosophy of psychiatry - Thornton, Tim (Timothy) (Oxford : Oxford University Press, 2007)
This book is a concise introduction to the growing field of philosophy of psychiatry. Divided into the three main aspects of psychiatric clinical judgement, values, meanings and facts, it examines the key debates about mental health care, and the philosophical ideas and tools needed to assess those debates.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psychiatry -- Philosophy